2020
DOI: 10.1002/aenm.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes and Interphases in Sodium‐Based Rechargeable Batteries: Recent Advances and Perspectives

Abstract: technologies. Unlike lithium, whose market is already very tight, sodium mineral deposits are almost infinite, evenly distributed worldwide, much easier to extract and thereby attainable at low cost. [1][2][3][4] If the realization of Na-rechargeable batteries could be practically possible, there will be nearly three orders of magnitude relaxation in the constraints on lithium-based resources, accompanied by sustainability, improved environmental benevolence, and cost reduction ( Table 1). Even more appealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
258
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(275 citation statements)
references
References 396 publications
(405 reference statements)
2
258
0
3
Order By: Relevance
“…To lower the flammability of organic liquid electrolytes, flame‐retardant compounds have been explored as solvents, cosolvents, or additives in SIB electrolytes. Generally, flame‐retardant solvents such as organic phosphates have poor passivation ability on electrodes, resulting in continuous degradation 11 . Zeng et al 57 reported nonflammable phosphate electrolyte (0.8 m NaPF 6 in trimethyl phosphate [TMP]) incorporating 10 vol% FEC.…”
Section: Electrolytes For All‐climate Sibsmentioning
confidence: 99%
See 2 more Smart Citations
“…To lower the flammability of organic liquid electrolytes, flame‐retardant compounds have been explored as solvents, cosolvents, or additives in SIB electrolytes. Generally, flame‐retardant solvents such as organic phosphates have poor passivation ability on electrodes, resulting in continuous degradation 11 . Zeng et al 57 reported nonflammable phosphate electrolyte (0.8 m NaPF 6 in trimethyl phosphate [TMP]) incorporating 10 vol% FEC.…”
Section: Electrolytes For All‐climate Sibsmentioning
confidence: 99%
“…In principle, Na‐based electrolyte salts have better chemical and thermal stability than Li salts. As a result, less of the acidic species are formed, mitigating the exothermic acid‐base reaction with SEI component Na 2 CO 3 as well as the corrosion toward cathode materials 11 . However, due to the lower Lewis acidity, Na‐based SEI compounds, which are mainly Na 2 CO 3 , NaF, and sodium double alkyl carbonate (NEDC), turn to be more soluble compared to Li counterparties, rendering that SEI layers in SIBs more vulnerable toward elevated temperatures 52,59 .…”
Section: Electrolytes For All‐climate Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reaction potential of sodium (À 2.71 V for Na/Na + ) is almost equivalent to that of lithium (À 3.04 V for Li/Li + ). [44][45][46][47][48] However, the energy density and cycle stability of SIBs are far inferior to those of LIBs. The main reason is that the radius of sodium ions is much larger than that of lithium ions, which causes large volume changes of the electrode materials during the charging and discharging process and leads to structural damage.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…[7][8][9] Investigations of SIB electrode materials are plentiful in the literature, [10][11][12][13][14][15] while there are much fewer electrolyte studies made, especially such that take a broader perspective. [16][17][18] SIB electrolytes more or less follow suit of LIB electrolytes. They are composed of cyclic carbonates e.g.…”
Section: Introductionmentioning
confidence: 99%